Hedonisme dan Impulsivitas Dalam Pembelian Produk Pakaian Melalui Cross Border E-Commerce - Pambudi, Yustikarani Julianti; Priyadi, Dhisa Tania; Rahmawati, Anisa; Ratana, Dhany Surya (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
Purpose– Aims to determine the effect of knowing hedonic motivation along with other factors, such as external and situational factors, on impulsive purchasing decisions for clothing products in cross-border e-commerce.Methodology– This research uses a quantitative approach by collecting data through random sampling questionnaires. All data collected was analyzed using Structural Equation Modeling processed using SmartPLS software.Findings– The results of this research show that hedonic motivation has no influence on impulse purchasing decisions for clothing products in cross-border e-commerce. In this research, the results showed that impulsive decisions were more influenced by the appearance on the cross-border e-commerce website, sales promotions and consumer time availability.Originality/Novelty– Providing novelty value to the phenomenon of impulse buying through cross border e-commerce arises not influenced by the user's hedonic motivation but other supporting factors, especially the quality of the cross border e-commerce website itself.Implications – The results of this research can be used by cross-border e-commerce development companies and e-commerce sellers to determine the right strategy for increasing the number of sales and improving service quality